2012
DOI: 10.1097/ppo.0b013e3182609490
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events in Cancer Genetic Testing

Abstract: Cancer genetic counseling and testing are now integral services in progressive cancer care. There has been much debate over whether these services should be delivered by providers with specialized training in genetics or by all clinicians. Adverse outcomes resulting from cancer genetic counseling and testing performed by clinicians without specialization in genetics have been reported, but formal documentation is sparse. In this review, we present a series of national cases illustrating major patterns of error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 33 publications
1
29
0
1
Order By: Relevance
“…This could lead to other providers with no specialized training in genetics taking on the responsibility of genetic testing, test interpretation and counseling. Such a situation may not be ideal since there have been several reports of adverse patient outcomes when non-genetics providers incorrectly ordered and interpreted genetic testing results and/or provided inadequate genetic counseling (Bensend et al 2013;Bonadies et al 2014;Brierley et al 2010Brierley et al , 2012. Additionally, although there is no clear evidence that the existing genetic counseling workforce cannot meet the demand for services even with the increased availability of genetic testing, the geographic distribution of genetic counselors is limited, particularly in some rural areas of the country (National Society of Genetic Counselors 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This could lead to other providers with no specialized training in genetics taking on the responsibility of genetic testing, test interpretation and counseling. Such a situation may not be ideal since there have been several reports of adverse patient outcomes when non-genetics providers incorrectly ordered and interpreted genetic testing results and/or provided inadequate genetic counseling (Bensend et al 2013;Bonadies et al 2014;Brierley et al 2010Brierley et al , 2012. Additionally, although there is no clear evidence that the existing genetic counseling workforce cannot meet the demand for services even with the increased availability of genetic testing, the geographic distribution of genetic counselors is limited, particularly in some rural areas of the country (National Society of Genetic Counselors 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, results suggest general adherence to NCCN surveillance guidelines despite lack proficiency in genetics knowledge (9, 10, 12). In contrast, negative outcomes reported through case reports when genetic testing occurs without adequate GC include misinterpretation of test results and inappropriate cancer screening/prevention recommendations(13). These observations require further systematic study in large unselected samples of BRCA carriers from diverse settings to enhance their generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…3032 A recent survey of 10,000 American physicians conducted by the American Medical Association found that only 26% understood how genetics tests could influence treatment decisions, and only 10% felt adequately trained to integrate genetic testing into their practice. 33 The new dimension of genome-informed medical care is likely to further unmask knowledge gaps in this area and increase the frequency of misinterpretations, thereby exposing patients to medical risk.…”
Section: Improving Genomic Literacy Among Care Providersmentioning
confidence: 99%